Studi Komprehensif Pembangkit Mikro Hidro dan Potensinya: Studi Kasus: A Comprehensive Study of Micro Hydro Plant and its Potential: A Case Study - Bhandari, Samir Raj (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2023)
The existing national grid network is unreliable in providing power to the rural hilly areas due to difficult to geographical structure of Nepal. Therefore, the demand ofMicro-hydro power plants are increasing in these areas of Nepal. MHPs produces up to 100kW and helps to distribute power to isolated communities. The main objective of this research is to study the technical and economic feasibility of micro hydropower in Gairibari Jharna, Kalika Municipality-08, Chitwan, Nepal.This project is an explanatory type research which is based on the primary data collected through questionnaires and field survey. Furthermore, upon the analysis of data collected from 41 out of 87 households, it showed positive interpretations.Through the qualitative and quantitative research, average power demand for each household was found to be 513.29 W leading to an average energy demand of 1.9 kWhr per day. Meanwhile, technical calculations showed the head available to be98m, discharge produced to be 0.24221m3/s and the ultimate design reflected the generated power to be 12 KW. Through the detail analysis of cost, budget for this projectwas NepaleseNRs 36,84,730 ($ 28,102.7) . After economic analysis of cost the payback period is calculated to be 15.37 years.